THEME AND THEMATIC PROGRESSION IN STUDENTS’ RECOUNT TEXTS - Yunita, Sri (Universitas Pendidikan Indonesia, 2018)
This study aims to investigate the Theme and Thematic progression patterns in students’ recount text in a state vocational school in Bandung. This study employs a descriptive-qualitative research design. The data were obtained from a collection of students’ texts. This study uses the theory of Theme system developed by Halliday (1994) and the theory of Thematic progression proposed by Eggins (2004) as the framework to analyze the data. The findings showed that the Theme and Thematic progression supports the character of Recount text written by the students to some extents: the Topical Theme represents the students’ ability to deliver what the text is about, the Interpersonal Theme helps students declare their personal comments, while the Textual Theme showed the students’ ability to develop the logical relationship between clauses and make their texts more cohesive and coherent. In terms of thematic progression patterns, the Theme Reiteration pattern signposts that the students tend to make the text focus by repeating the same element as Themes; the Zig Zag pattern showed that the students introduce newly information by promoting the Rheme in a clause to the Theme in the subsequent clause, and the Multiple Theme pattern specifies that the students develop the texts well according to the prior plan before writing those ideas in the text.